CHANGES IN INCOME DISPARITIES DUE TO INFORMATION AND COMMUNICATION TECHNOLOGY BETWEEN RIAU PROVINCE, WEST KALIMANTAN PROVINCE, SOUTH SUMATERA PROVINCE - Nuril Nadia Aditia; Sishadiyati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Indonesia is a country that has quite high income disparities between regions. The occurrence of differences in income disparity conditions in several provinces in Indonesia, especially in Riau Province, West Kalimantan Province and South Sumatra Province, cannot be separated from many factors, one of which is the role of ICT. ICT plays an important role in supporting economic growth and overcoming income disparities, so this research aims to determine the structure of the economy, determine the condition of income disparities, and determine the contribution of ICT to income disparities in Riau Province, West Kalimantan Province, and South Sumatra Province in 2010-2022. This research uses a quantitative approach with regional Klassen typology analysis methods, Wiliamson index analysis, and binary logistic regression analysis. The research results show that Riau Province is included in the category of developed but depressed regions, while West Kalimantan Province and South Sumatra Province are included in the category of rapidly developing regions. The average income disparity during the 2010-2022 period, Riau Province reached 0.51%, West Kalimantan Province was 0.25%, and South Sumatra Province was 0.58%. ICT contributes to income disparities by 26.1%, with an analysis of the influence of ICT indicators, namely households that own/control a cell phone have a significant positive effect on income disparities, households that own/master a computer have a negative and insignificant effect, and the percentage of households that accessing the internet in the last 3 months had a negative and significant effect